AB1275 Ultrasound evaluation of the hands and wrists joints: a proposal of a new 10-joint ultrasound score for diagnosis and assessment of early rheumatoid arthritis patients. (23rd January 2014) - Luz, K.; Furtado, R.N.V.; Pinheiro, M.M.; Petterle, G.S.; Natour, J.
Abstract : Background: Previous reports have described the use of ultrasound (US) scores to evaluate rheumatoid arthritis (RA). However, no previous studies have used the ultrasound assessment of the hand and wrist joints for diagnosis of early RA patients. Objectives: To evaluate the value of a new standardized ultrasound score based on 10 joints of the hand and wrist for diagnosis and assessment of early RA patients. Methods: Fifty-one early RA patients without any disease-modifying antirheumatic drug (DMARD) treatment were enrolled on the study. The patients underwent ultrasound (US) examinations by 10 ultrasound score using a MyLab60 (Esaote, Biomedica – Genoa, Italy), equipped with a broadband linear probe (6-18 MHz). The following joints of both hands were assessed (918 joint recesses): wrist (radiocarpal, midcarpal and ulnocarpal joints), second and third metacarpophalangeal and proximal interphalangeal joints. Synovitis and synovial vascularity were scored semiquantitatively (grade 0–3) by gray-scale (GS) and power Doppler (PD) ultrasound respectively. The scoring range was 0–18 for the "presence" of GS synovitis (GSUS) and PD synovitis (PDUS) and the range was 0-54 for the semiquantitative scoring system of GS (GSSQ) and PD (PDSQ). Another physician (blinded for ultrasound examinations) performed disease activity assessment using DAS28 and the SDAI. The laboratory evaluation was obtained with C-reactive protein (CRP) level and erythrocyte sedimentation rate (ESR). Results: The mean ± duration of the symptoms was 7, 58 (±3, 59) months, all patients have high activity disease with mean ± DAS 28 of 6, 50 (±1, 29) and SDAI of 46, 44 (±16, 52). The mean ± CRP level was 14, 17 (±1, 29) mg/L and the mean ± ESR level was 30, 78 (±26, 07) mm/hour. The mean ± GSUS, PDUS in the 10 joints was 12, 47 (±2, 76) and 6, 72 (±4, 17), respectively. The mean ± GSSQ was 27, 21 (±8, 99) and the mean ± PDSQ was 13, 05 (±8, 29). There was no correlation between GSUS or GSSQ and DAS28, SDAI and ESR. However, a significant correlation was observed between GSUS and GSSQ and CRP (r=0.368, p<0.05; r=0.326, respectively). There was a significant correlation between PDUS and DAS 28, SDAI, ESR and CRP (r=0.330, p<0.05; r=0.316, p<0.05; r=0.343, p<0.05, r=0.527, p<0.05, respectively). Also there was a correlation between the PDSQ and DAS28, SDAI, ESR and CRP. (r=0.304, p<0.05; r=0.288, p<0.05; r=0.307, p<0.05, r =0. 537 p<0.05, respectively). Conclusions: There was significant correlation between the synovial vascularity (PDUS and PDSQ) of 10 joint ultrasound assessments and disease activity in early RA patients. A 10-joint US score can be a new tool for evaluating joint inflammation and follow-up of early RA patients. References: Backhaus M, Ohrndorf S et al. Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: a pilot Project. Arthritis Rheum. 2009 Sep 15;61(9):1194-201. Perricone C, Ceccarelli F et al. The 6-joint ultrasonographic assessment: a valid, sensitive-to-change and feasible method for evaluating joint inflammation in RA. Rheumatology (Oxford). 2011 Dec 30. Disclosure of Interest: None Declared